Growth response of Emiliania huxleyi to ocean alkalinity enhancement - Faucher, Giulia; Haunost, Mathias; Paul, Allanah Joy; Tietz, Anne Ulrike Christiane; Riebesell, Ulf (Biogeosciences, 2025)
The urgent necessity of reducing greenhouse gas emissions is coupled with a pressing need for widespread implementation of carbon dioxide removal (CDR) techniques to limit the increase in mean global temperature to levels below 2 °C compared to pre-industrial times. One proposed CDR method, ocean alkalinity enhancement (OAE), mimics natural rock weathering processes by introducing suitable minerals into the ocean, thereby increasing ocean alkalinity and promoting CO2 chemical absorption. While theoretical studies hold promise for OAE as a climate mitigation strategy, careful consideration of its ecological implications is essential. Indeed, the ecological impact of enhanced alkalinity on marine organisms remains a subject of investigation, as it may lead to changes in species composition. OAE implicates favorable conditions for calcifying organisms by enhancing the saturation state of calcium carbonate and decreasing the energetic costs for calcification. This may affect marine primary production by improving conditions for calcifying phytoplankton, among which coccolithophores play the leading role. They contribute < 10 % to the global marine primary production but are responsible for a large proportion of the marine calcite deposition. While previous research has extensively studied the effects of ocean acidification on coccolithophores, fewer studies have explored the impacts of elevated pH and alkalinity. In this context, we studied the sensitivity of Emiliania huxleyi, the most widespread coccolithophore species, to ocean alkalinity enhancement in a culture experiment. We monitored the species' growth and calcification response to progressively increasing levels of total alkalinity (TA). Above a change in total alkalinity (ΔTA) of ∼ 600 µmol kg−1, as CO2 concentrations decreased, the E. huxleyi growth rate diminished, suggesting a threshold CO2 concentration of ∼ 100 µatm necessary for optimal growth. The cellular calcite to organic carbon ratio (PIC : POC) remained stable over the total alkalinity range. Due to the decreasing growth rate in response to alkalinity enhancement, total carbonate formation was lower. OAE is rapidly advancing and has already reached the field-testing stage. Hence, our study contributes to the most critical part of investigations required to comprehend potential biological implications before large-scale OAE is adopted.